STEPONS SEIĻS AND HIS ARCHIVES IN THE NATIONAL LIBRARY OF LATVIA - Limane, Lilija (Via Latgalica, 2017)
Latgalian teacher, publicist and cultural history researcher Stepons Seiļs (1909–1979) devoted his whole lifetime to collect cultural facts about Latgale. He was working with a relentless dedication, and, despite the pressure from those in power, he remained loyal to the Latgalian language and supportive of the idea that Latgalian has to be preserved in print. S. Seiļs can be characterized as a man of deep and lasting interest in publishing of Latgalian books and a persistent and zealous collector of cultural heritage. In his home „Kļovi” in Makašāni parish he created an impressive library of Latgalian works with almost complete collection of books, sizable sets of major newspapers, old manuscripts and a large amount of manuscripts and other materials about cultural figures. The National Library of Latvia obtained the first part of archival materials belonging to S. Seiļs in 1974 from the public prosecutor’s office of the Latvian SSR. The Soviet police confiscated printed publications and manuscripts from the home of S. Seiļs „Kļovi” in Rēzekne district during the search and seizure operation of July 1–3, 1974 with the purpose to find anti-Soviet literature. After checking into Seiļs’ materials, the prosecutor’s office decided not to bring any charges against S. Seiļs. The library staff analysed the printed materials and scripts and reached an agreement with S. Seiļs to keep 54 units of manuscripts in its collection and in the Department of Rare Books and Manuscripts, where a personal archive (RXA96) of S. Seiļs would be formed. The library also made microfilms of his returned materials, partially compensating the owner for these writings. The personal archive includes materials on activities of the Central Society of Latgalian Teachers and other cultural organizations. At the same time, 16 copies of microfilms were made of the essays of S. Seiļs and other Latgalian author manuscripts. Taking the sociopolitical situation of the times into account, the library mostly kept periodical publications from the 1920’s and 1930’s that met all the criteria of special collection according to the instructions set by Main Administration for Literary and Publishing Affairs (Glavlit). The remaining publications and manuscripts, including diaries, letters and studies about personalities were taken back to „Kļovi” and returned to the owner. The most of S. Seiļs’ private library was purchased after his death from his heirs. The cultural heritage includes printed matter and an extensive archive of manuscripts. Printings include several of the so-called Latgalian „contrafactions” (books, which were printed during the prohibition of Latin script in Latgale and had counterfeit printing dates on them). These rare specimens were stored in the collection of the Department of Rare Books and Manuscripts. The rest of the books following the principles of collection management were included in the general book collection. Some 254 manuscripts were added to the personal archive of S. Seiļs. Manuscript archive was enriched with some outstanding printed masterpieces of the period of ban on printing, as well as creative materials of S. Seiļs and other authors, and a wide range of correspondence. Information about eminent people of Latgalian descent, put together in the „cases” became available to readers. It includes the information on every notable person of Latgalian descent or those connected to Latgalian culture in the 20th century. His collection can reasonably be regarded as the archive of Latgalian people. In 2000, the library received 13 folders with deposited materials from Pēteris Seiļs, the son of S. Seiļs. Currently, the personal archive of S. Seiļs holds 339 manuscripts. These materials provide a rich source of information for researchers and those, who are interested in Latgalian history.